IGS region based phylogenetic analysis to resolve interspecific relationships within Fusarium oxysporum f. sp. ciceris - Priyanka, Kumari; Dubey, S C; Singh, A K (Indian Journal of Plant Protection, 2020)
The resolving power of the Intergenic spacer region (IGS) region of Fusarium oysporum f. sp. ciceris (Foc) isolates causing wilt in chickpea representing various races and agro-ecological region of origin was undertaken to evaluate relationships within the population of the pathogen and to find the correlation between origins and/or races of the pathogen by using cluster analysis drawn from IGS-RFLP (Restriction fragment length polymorphism) banding pattern as well as by partial IGS sequence. The amplified IGS region of the isolates was digested with the 11 restriction enzymes separately. Of these five enzymes,viz., EcoRI, AvaI, BsmAI, HphI and MspI gave specific banding patterns and were considered suitable to resolve interspecific relationship within Foc isolates. The combined UPGMA analysis of the restriction patterns obtained from these 5 enzymes as well as bootstrap neighborjoining analysis based on partial IGS sequence grouped the Foc populations into various subclusters, showed genetic variation within the isolates. More or less similar grouping patterns were obtained from IGS sequence and RFLP analyses, therefore RFLP could be used as an alternative of sequencing. Apart from that, the groups did not correspond to the place of origin and races of the pathogen. The information generated in the present study would facilitate the better understanding of evolutionary relationship of wilt producing populations of the pathogen.